TINDAK PIDANA ATAS PERAMPASAN KENDARAAN BERMOTOR OLEH PERUSAHAAN LEASING TERHADAP NASABAH DI KOTA SAMARINDA - Ardiansyah Hamid (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
AbstractLeasing according to Perpres No. 9 of 2009 concerning financial institutions is a financial institution in the form of capital goods, both for leasing with option rights (finance lease) or leasing without operating rights for tenants to use. for business (lessee). During a certain period during a certain period based on installment financing.Criminal liability for the seizure of motor vehicles by leasing companies to customers in Samarinda City using the services of the Debt Collector both before or after committing criminal acts in the form of threats, and or abuses mentioned above to the debtor is an individual responsibility. Without any connection to companies that use their services in billing. Finance and the consumer in implementing a motor vehicle loan agreement should be based on the principle of good faith